Aprendizagem colaborativa mediada pelo Moodle como apoio ao ensino de licenciatura em computação do IFTO - Campus Araguatins - Melo, Ramásio Ferreira de (2015)
This study aimed to analyze the potential integration of Moodle to support the teaching of the Degree in Computer course, to promote interaction and collaboration network. We adopted a methodological qualitative and quantitative approach, based on action research principles in the period from March 2013 to March 2015 were used as data collection instruments, participant observation and online questionnaires Survey type applied to teachers Bachelor of Computing IFTO - Campus Araguatins and students of the 1st period, enrolled in the course "Computers and Society", semester 2014.1. For the organization and analysis of the collected data adopts a matrix system: Dialogic-problem-Matrix (MDP), Theme-Organizing Matrix (MTO), Theme-Analytical Matrix (MTA). Conclusively, AVEA Moodle, proved to be a great potential platform to promote the production of collaborative knowledge through tools such as Wiki and Forums thread. Using Moodle provided an opportunity fluency of teachers and students in educational technology and extended learning spaces beyond the classroom.